Dukungan Psikososial pada Remaja Melalui Sosialisasi dan Skrining Sehat Jiwa: Psychosocial Support in Adolescents Through Socialization and Mental Health Screening - Saripah, Eli; Aminuddin, Aminuddin; Siregar, Hasbunsyah (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2024)
Introduction: Mental health is an inseparable part of physical health and is the main element in supporting the realization of a complete quality of human life. During adolescence, biological, psychological and social changes occur, but generally the physical maturation process occurs faster than the mental (psychosocial) maturation process. Adolescents are faced with various changes that are occurring within themselves and development targets that must be achieved according to their age. The aim of this community service activity is to increase youth mental health resilience with mental health literacy with a youth mental health support program through communication, information and education activities. This method takes the form of psychosocial support for teenagers through socialization and mental health screening. This activity was attended by 68 students who were given questionnaires before and after the activity. The results of the analysis increased the average student knowledge score regarding adolescent psychosocial support with a pre-test score of 48.28% and a post-test of 72.55%. The results of the SRQ-29 screening showed that the majority of students experienced post-traumatic stress disorder due to natural disasters in the area where they lived. The community service team's conclusion is that the process has been carried out based on the planned stages. Suggestions for students to further increase literacy regarding the development of psychosocial support for adolescents.